Kontribusi Electronic Word of Mouth , Citra Merek terhadap Keputusan Pembelian pada Mie Setan: Studi Pada Followers @Food_Fess Di Twitter - Dadang Krisdianto; Dwi Awalia Arisca (STIA MALANG, 2023)
This research used a quantitative method and descriptive analysis to determine data trends, followed bycorrelation and regression tests, and then path analysis to calculate the direct influence of electronicword of mouth (X1) on purchase decisions (Y) at 0.1982 = 0.0392 or 3.92%. The magnitude of brandimage's (X2) direct contribution to purchase decisions (Y) is 0.5272 = 0.2777 or 27.77%. The combinedcontribution of electronic word of mouth (X1) and brand image (X2) in influencing purchase decisions(Y) simultaneously is 0.442 = 44.2%. The remaining 55.8% is influenced by other factors not explainedin this research. The importance of the contributions of electronic word of mouth (X1) and brand image(X2) in influencing purchase decisions (Y).